DEVELOPING AN ACCREDITATION SYSTEM FOR LIS PROFESSIONAL EDUCATION PROGRAMMES IN SOUTHEAST ASIA: ISSUES AND PERSPECTIVES - Khoo, Christopher; Majid, Shaheen; Chaudhry, Abdus Sattar (Malaysian Journal of Library and Information Science, 2003)
The paper examines some of the issues involved in developing accreditation standards and procedures for Library and Information Studies (LIS) professional education programs in Southeast Asia. The accreditation standards of the American Library Association (ALA), Australian Library and Information Association (ALIA), Chartered Institute of Library and Information Professionals (CILIP) (UK) and International Federation of Library Association (IFLA) are examined, and the main features and content of the standards are discussed with respect to the Southeast Asian context. The four major aspects/activities in the accreditation process, dialogue, self-evaluation, documentation and external review, are also discussed. The paper also presents summary results of a questionnaire survey of LIS schools in Southeast Asia that was carried out in 2002 to gather views on various accreditation issues and expected problems. An organisational model is proposed for the accreditation of LIS degree programmes in Southeast Asia under the oversight of Congress of Southeast Asian Librarians (CONSAL).